Acoustics : Basic Physics, Theory, and Methods. - Filippi, Paul (Elsevier, 1998)
The book is devoted to the very basis of acoustics and vibro-acoustics. The physics of the phenomena, the analytical methods and the modern numerical techniques are presented in a concise form. Many examples illustrate the fundamental problems and predictions (analytic or numerical) and are often compared to experiments. Some emphasis is put on the mathematical tools required by rigorous theory and reliable prediction methods.